Hypoxia-inducible factor (HIF1A and HIF2A), angiogenesis, and chemoradiotherapy outcome of squamous cell head-and-neck cancer - Koukourakis, Michael I; Giatromanolaki, Alexandra; Sivridis, Efthimios; Simopoulos, Constantinos; Turley, Helen; Talks, Kate; Gatter, Kevin C; Harris, Adrian L (International journal of radiation oncology, biology, physics, 2002)
Hypoxia-inducible factors HIF1alpha and HIF2alpha (HIFalphas) regulate the expression of a variety of genes encoding proteins related to angiogenesis and to anaerobic metabolism of cells exposed to hypoxic stress. Their putative role as markers of clinically relevant hypoxia and, therefore, as predictors of response to chemoradiotherapy is herein examined. Using immunohistochemistry, we assessed the expression of HIFalphas in normal head-neck mucosa and in 75 cancer specimens from patients with locally advanced squamous cell head-and-neck cancer (SCHNC), treated with concurrent carboplatin chemoradiotherapy. Head-and-neck mucosa from normal individuals did not show any HIF1alpha or HIF2alpha reactivity. SCHNC showed a varying expression of HIFalphas ranging through negative reactivity, to weak or focally strong cytoplasmic reactivity, or to strong diffuse cytoplasmic/nuclear reactivity. Fifty-two percent and 33% of cancer samples showed the latter expression pattern for HIF1alpha and HIF2alpha, respectively, and were considered to bear "high" HIF reactivity. Bone/cartilage involvement was more frequent in tumors with high HIF1alpha expression (p = 0.05). HIF1alpha and HIF2alpha overexpression were significantly associated with high microvessel density (p = 0.002 and 0.02, respectively) and with VEGF expression (p = 0.01 and 0.005, respectively). HIF1alpha was related to high thymidine phosphorylase expression (p = 0.03), whereas VEGF/KDR-activated tumor vasculature was significantly more frequent in HIF2alpha-overexpressing tumors (p = 0.02). High HIF1alpha and HIF2alpha were associated with incomplete response to chemoradiation (p = 0.007 and p = 0.02, respectively). In univariate analysis, high HIF1alpha and HIF2alpha expression were significantly associated with poor local relapse-free survival (p = 0.003 and 0.003, respectively) and with poor overall survival (p = 0.05 and 0.001, respectively). In multivariate models, HIF2alpha expression was an independent prognostic factor. In biopsies performed after the delivery of 20 Gy of radiotherapy, upregulation of HIFalphas was noted in some cases. It is concluded that the overexpression of HIFalphas in SCHNC is related to locally aggressive behavior, to intensification of angiogenesis, and to an important resistance to carboplatin chemoradiotherapy.